1990
DOI: 10.1159/000243226
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone May Modulate Hepatic Somatomedin C Production in Newborn Calves

Abstract: We have studied the possible influence of steroid hormones and a β-agonist (clembuterol) on hepatic insulin-like growth factor 1 (IGF1) production in young calves. For this purpose nine 20- to 40-day-old Holstein × Friesian male calves were fitted with chronically indwelling catheters in hepatic and portal veins and hepatic artery. Estradiol induced a simultaneous increase in plasma growth hormone (GH nmol/l) and IGF1 (nmol/l) levels (0.35 ± 0.05 vs. 0.10 ± 0.01 in control calves; 9.5 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Because glucocorticoids are important for neonatal maturation (7), reduced GH concentrations after Dexa treatment in our study might indicate enhanced maturation of the somatotropic axis, as shown in neonatal pigs (10). On the other hand, cortisol treatment in 1-mo-old calves did not affect plasma GH concentrations (15). Because glucocorticoids have stimulatory and inhibitory effects on pituitary GH production and release (38), effects of glucocorticoids on GH secretion may depend on the developmental status.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Because glucocorticoids are important for neonatal maturation (7), reduced GH concentrations after Dexa treatment in our study might indicate enhanced maturation of the somatotropic axis, as shown in neonatal pigs (10). On the other hand, cortisol treatment in 1-mo-old calves did not affect plasma GH concentrations (15). Because glucocorticoids have stimulatory and inhibitory effects on pituitary GH production and release (38), effects of glucocorticoids on GH secretion may depend on the developmental status.…”
Section: Discussionmentioning
confidence: 58%
“…However, our data correspond to findings in neonatal pigs (10) and growing bulls (43) treated with Dexa. However, Coxam et al (15) did not find an effect of cortisol on plasma IGF-I concentrations in calves, and Dexa decreased plasma IGF-I concentrations in cows and finishing calves (2,33). Therefore, effects of glucocorticoids on IGF-I plasma concentrations are variable and may depend on treatment-dose (34) and age (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, neonatal calves are able to produce IGF‐1 since IGF‐1 mRNA is expressed in liver, GIT, spleen, thymus, lymph nodes and kidney (Cordano et al., 2000; Pfaffl et al., 2002; Ontsouka et al., 2004a–c). Administration of bovine GH increases plasma IGF‐1 concentrations (Coxam et al., 1988; Grütter and Blum, 1991b; Hammon and Blum, 1997b) and there are significant changes of IGF binding proteins 1–3 in response to differences in feeding and endocrine treatments (Hammon and Blum, 1997b; Sauter et al., 2003). Although the GH‐IGF‐1 axis in neonatal calves is basically functional, the system is not fully mature because hepatic IGF‐1 expression in neonatal calves is small (Cordano et al., 2000; Pfaffl et al., 2002), and GH effects on the IGF systems are markedly smaller in neonatal calves than in older cattle.…”
Section: Components Of Colostrummentioning
confidence: 99%
“…From day 3 onwards, the calves were fed daily at 08.00 and at 16.00 h. Additionally, the GrFD + and GrCD + calves were injected intramuscularly with DEXA (30 Ìg/kg/day, DEXA TAD; Lohmann Animal Health, Cuxhaven, Germany) twice daily at feeding times from day 1 to day 4. The dose of DEXA was chosen based on previous studies in animals [3,18]. D-Xylose (0.5 g/kg) was added to the morning meal of all calves on day 3 to study the intestinal xylose absorption capacity.…”
Section: Animals Husbandry Feeding and Experimental Proceduresmentioning
confidence: 99%
“…In each feeding group, half of the calves were treated by DEXA (GrCD + and GrFD + ). a The calves were treated twice daily at feeding times; the dose of DEXA was chosen according to previous studies in neonatal calves [18]. b Colostrum and formula were fed in amounts of 6% of body weight.…”
Section: Introductionmentioning
confidence: 99%